Surface-enhanced Raman scattering of Ag–Au nanodisk heterodimers - Liusman, Cipto (2013)
We report the fabrication of Ag–Au nanodisk heterodimers based on the modified on-wire lithography method and study their surface-enhanced Raman scattering (SERS) properties experimentally and theoretically. The effects of disk thickness and gap size on SERS are explored. The SERS properties of the optimized heterodimers are compared with those of the respective homodimers and single nanodisks excited at 633 and 488 nm. We found that the enhancement factor (EF) of Ag–Au heterodimers is greater at 633 nm than that at 488 nm, while their EF is between those of the Ag–Ag and Au–Au homodimers. At 488 nm excitation, the calculation indicates that the plasmon energy can be transferred from the Ag disk to the Au disk.